TRACE OF MARITIME CULTURE AND TRADE OF THE MAJAPAHIT KINGDOM - Anita (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2023)
The problem in this research is how the hegemony of the Majapahit kingdom was and how trade was during the Majapahit kingdom, with the aim of the research being to find out the hegemony and trade of the Majapahit kingdom. The research method used is the library study research method, which means collecting information that is relevant to the topic or problem that is the object of research. The research results show that the Majapahit kingdom was the largest Hindu-Buddhist kingdom in Indonesia which was founded by Raden Wijaya in 1293-1527 in the 13th to 16th centuries. During the Majapahit kingdom, trade was not carried out freely. To regulate the rhythm of trade, along with taxes, in the royal bureaucracy there was a rakryan kanuruhan or "grand chancellor" who was tasked with managing foreign traders or merchants from other islands in the archipelago. The development of maritime trade in the Java Sea was closely tied to India in the early days, then expanded in the 3rd to 6th centuries with China. Specifically with China, trade is carried out by selling or purchasing unloaded cargo destined for or originating from foreign markets, or selling local products. Trading activities are focused on ports. Most imported goods are channeled into the country through a dense market circulation network.